Human Capital and Optimal Redistribution - Winfried Koeniger; Julien Prat (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We show that more human capital improves incentives in a standard optimal taxation problem: common assumptions about preferences and technology imply that the disutility of labor decreases less strongly in unobserved ability if agents have more human capital. Human capital thus reduces the informational rents of high ability types and relaxes the incentive constraints. Since parents do not take the effect of human capital on incentives into account when choosing how much to invest into their children, there is a rationale for education subsidies.
Keywords: E24; H21; J24; 330